INVESTIGATION OF THE INTERNAL RISK FACTORS INFLUENCE ON THE TIME OF THE ISCHEMIC STROKE ONSET - Volosovets, A.O.; Zozulya, I.S. (World of Medicine and Biology, 2019)
The purpose of the present study was to determine the effect of internal modified risk factors at the time of the ischemic stroke onset. We performed a clinical, neurological and neuroimaging study of 300 patients who suffered an acute ischemic stroke (men - 196, women - 104) aged 42 to 84 years (average age - 65.2 ± 8.7 years). The factor of arterial hypertension was observed among all groups of patients. Тhe factor of the arrhythmia had a clear association with the daytime and evening period of occurance of stroke (groups 1 and 2), which is exactly the same as the appearance of the cardioembolic subtype of ischemic stroke. The factor of atherosclerosis has demonstrated great importance for all groups. At the same time, the factor of diabetes showed a significant increase just for patients in group 3 (82.9%), which confirms the association of glycemic metabolic disorders with autonomic vascular regulation at night. The predictor of overweight has shown a strong presence in all patients, but a clear tendency prevalence is in the 2nd and 3rd groups. The level of cholesterol among patients with stroke, had a slightly different trend - in the 1st group there was an insignificant level of hypercholesterolemia (5.4 ± 0.5 mmol / l); In the 2nd group was higher level of hypercholesterolemia (7.3 ± 0.7 mmol / l); In the 3rd group, despite the relative prevalence of overweight, we have discovered a moderate level of hypercholesterolemia (5.8±0.5 mmol/l). Internal risk factors play an important role in the occurrence of cerebral ischemia. Also they have shown high level of nonspecificity in detecting the effect on the time of stroke onset.